ANALISIS GAYA BAHASA PERBANDINGAN DALAM HIKAYAT IBRAHIM HASAN KARYA NURMAN SYAMHAS - Deswita, Dinda; Harun, Mohd.; Subhayni, Subhayni (JIM Pendididikan Bahasa dan Sastra Indonesia, 2018)
ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan jenis-jenis gaya bahasa perbandingan yangterdapat di dalam hikayat Ibrahim Hasan karya Nurman Syamhas dan mendeskripsikangaya bahasa perbandingan yang paling dominan muncul di dalam hikayat Ibrahim Hasankarya Nurman Syamhas. Sumber data dalam penelitian ini adalah hikayat Ibrahim Hasankarya Nurman Syamhas. Metode yang digunakan dalam penelitian ini adalah metodedeskriptif kualitatif. Pengumpulan data dilakukan dengan teknik dokumentasi. Hasilanalisis yang telah didapatkan dalam hikayat Ibrahim Hasan karya Nurman Syamhasdalam gaya bahasa perbandingan,yaitujenis gaya bahasa perbandingan yang berbentukmetafora, ironi, antonomasia, alegori, parabel, fabel, personifikasi. Gaya bahasaperbandingan yang paling dominan muncul dalam hikayat tersebut adalah gaya bahasametafora.Kata kunci: hikayat, gaya bahasa perbandingan, ibrahim hasan.ABSTRACTThe study is entitled "Comparative Language Style in the saga of Ibrahim Hasan byNurman Syamhas". The formulation of this research problem is (1) what kind ofcomparative language style is contained in the story of Ibrahim Hasan by NurmanSyamhas? and (2) what is the most dominant language style in the story of Ibrahim Hasanby Nurman Syamhas? The aims of this study are (1) to describe the types of comparativelanguage styles contained in the Ibrahim Hasan saga by Nurman Syamhas and (2) todescribe the most dominant type of comparative language in the story of Ibrahim Hasan byNurman Syamhas. The method used in this research is qualitative descriptive method. Theresult of analysis that has been obtained in the story of Ibrahim Hasan by NurmanSyamhas of comparative language style,. Types of comparative language styles and thenumber of types of comparative language styles are, metaphorical, irony, antonomasia,allegory, parables, fable, and personification. The most dominant language stylecomparison that appears in the saga is the style of the metaphorical language.Keywords: comparative language style, saga, ibrahim hasan.